Sperm selection with Annexin-V coated polystrene bead technique (APB-Tech): A novel and reliable method for the microscopic selection of viable and non-apoptotic sperm to be used for intracytoplasmic sperm injection - Karabulut, Seda; Camci, Irem Yalim; Atambay, Can; YiGit, Pakize; Keskin, Ilknur (Elsevier Science Inc, 2022)
Infertility is a growing health problem that affects 20% of couples who want to conceive. `Intracytoplasmic sperm injection' (ICSI) is a commonly used assisted reproduction treatment technique that offers the couples to overcome a wide variety of infertility reasons, including female, male and unexplained infertility. A crucial step in ICSI is choosing the correct spermwith the highest potential to form a healthy embryo and thus a healthy offspring. The sperm selection strategies aim to obtain a sperm population with better motility and morphology, which are insufficient to predict a sperm's reproductive potential. The elimination of apoptotic sperms, which is shown to be higher in infertile males and which is shown to affect embryo development and reproductive cohort significantly should also be included in the selection strategies. Among all sperm selection methods, there are only a few which can eliminate apoptotic sperm, but because they need extra types of equipments, a long training period, and high costs, they couldn't find place in the most commonly used techniques in an IVF lab. Selecting the non-apoptotic sperm cells will help us choose a sperm that is more likely to be chosen by the natural selection mechanisms and thus will help to mimic the natural conception more. The study aimed to develop a novel, easy and a harmless individual sperm selection technique to enable choosing non-apoptotic viable sperm cells via light microscopy without any need for extra equipment, education and cost to be used for ''ICSI'. The technique is based on the binding ability of Annexin-V covered polystrene beads to the externalized phosphatidylserine at the outer leaflet of an apoptotic sperm's plasma membrane. After Annexin-V covered polystyrene beads were prepared, beads obtained were attached to BALB-c mice sperm, and the technique is optimized to obtain the most efficient attachment conditions. The results are then compared with the results of four well-known reliable apoptosis detection techniques to test the validity and sperm survival test to test the toxicity of the technique. The method is proven to be '''reliable' by comparing it with the results of well-known techniques, including TUNEL and SCSA (sperm chromatin structure assay), and '''safe' by showing its non-toxicity via sperm survival test (SST). In addition, the method enables the selection of sperm cells more closer to naturally-chosen ones from a pool of sperm that should not be allowed to be randomly chosen during microinjection. To date, it was impossible to distinguish a non-apoptotic sperm without harming it or without needing additional equipment other than a routine IVF lab and extra training other than routine andrology work.
Keywords: Sperm selection; Apoptosis; ICSI; APB-Tech; DNA fragmentation